Problems and perspectives of yambased cropping systems in Africa - Ekanayake, I.J.; Asiedu, Robert (Informa UK Limited, 2003)
Yams (Dioscorea spp.) constitute an important starchy staple in sub-Saharan Africa (SSA) where food security for a growing population is a critical issue. Mixed cropping in yam based systems is the norm in the region and productivity of yams in these systems is below potential. It is concluded that there is much scope for improvement of yam based cropping systems in SSA in order to meet the needs of the region. The strategy of crop breeding to select yam varieties suitable for various cropping systems must consider a truly multidisciplinary systems approach. Further manipulation must be made to tuber dormancy to expand flexibility in field propagation in different cropping systems and improve storage and marketing. The sustainability of yam based cropping systems in SSA could improve if agronomic research was focused on strategies for improving soil fertility, weed and pest management including design of cropping systems and suitable rotations.